Prediksi Impor Hasil Pertanian (Sayuran) Menurut Negara Asal Utama Menggunakan Algoritma Levenberg-Marquardt - Achmad Daengs GS; Irma Hakim; Fitri Anggraini (LPPM STIKOM Tunas Bangsa, 2024)
Vegetables are very important as a source of nutrition for society and provide various vitamins, minerals, fiber and antioxidants needed to maintain human health. This research aims to predict imported production of vegetable crops by main country of origin in 2024 using the Levenberg-Marquardt algorithm. This algorithm was chosen because of its ability to integrate historical data and current information, as well as considering risk factors that impact vegetable import production. Historical data regarding imported production of vegetable crops from the main countries of origin used covers the period 2014 to 2022. The data is processed from customs documents of the Directorate General of Customs and Excise (PEB and PIB) and quoted from the Indonesian Statistics Publication. The vegetable import production prediction model was evaluated using accuracy level metrics. The research results are expected to provide reliable and accurate predictions for vegetable import production based on the main country of origin in 2024. The accuracy resulting from this research is 91% and the MSE level is 0.10042088158. Vegetable import production according to the main country of origin based on predicted results is expected to decline when compared with the previous year (2014-2022). These predictions provide a more detailed understanding to stakeholders such as farmers, producers, government and industry players in planning production, managing resources, allocating budgets and making effective decisions. This research also has the potential to contribute to the development of knowledge, especially in the development of more advanced and efficient prediction methods. This applies both to imported vegetable production and to other agricultural sectors, by utilizing the Levenberg-Marquardt algorithm.